Linear low-density polyethylene/silica micro- and nanocomposites: dynamic rheological measurements and modelling (eXPRESS Polymer Letters, 2010)
Linear low-density polyethylene (LLDPE) based composites were prepared by melt compounding with 1, 2, 3 and 4 vol% of various kinds of amorphous silicon dioxide (SiO2) micro- and nanoparticles. Dynamic rheological tests in parallel plate configuration were conducted in order to detect the role of the filler morphology on the rheological behaviour of the resulting micro- and nanocomposites. A strong dependence of the rheological parameters from the filler surface area was highlighted, with a remarkable enhancement of the storage shear modulus (G′) and of the viscosity (η) in fumed silica nanocomposites and in precipitated silica microcomposites, while glass microbeads only marginally affected the rheological properties of the LLDPE matrix. This result was explained considering the formation of a network structure arising from particle-particle interactions due to hydrogen bonding between silanol groups. A detailed analysis of the solid like behaviour for the filled samples at low frequencies was conducted by fitting viscosity data with a new model, based on a modification of the original De Kee-Turcotte expression performed in order to reach a better modelling of the high-frequency region.